Exploring the effects of single and dual phase culturing on the concentrations of Southern Ocean sea-ice algae and transporting living sea-ice algae from the Southern Ocean to land-based research facilities - Hambrock, Mark (Department of Chemical Engineering, 2022)
Sea ice is a complex material with a significant impact on the global climate. Understanding the development of sea-ice properties based on the change in growth conditions is vital for the development of predictive models, which are key to providing forecasts of the influence global warming will have on sea ice. Algae found in sea ice form an important part of the oceanic food network, providing secondary producers with a source of food, particularly during winter, and are suspected of seeding algae blooms during spring and summer. Researching sea ice and sea-ice algae in situ is an expensive and logistically difficult undertaking, especially in the Southern Ocean. Consequently, many researchers elect to perform research on artificial sea ice, where conditions are more controlled while logistical and financial constraints are reduced. Despite the extent to which sea-ice research has been performed on artificial sea ice, relatively little research on sea-ice algae in artificial sea ice has been done. Sea-ice algae are strongly affected by the temperature, salinity, nutrient availability and intensity of photosynthetically active radiation in their environment. This makes the transportation of living sea-ice algae difficult. Little documentation of transportation of living sea-ice algae exists, with most of the laboratory research of sea-ice algae being performed on single-species liquid cultures. Such research is important but fails to address the complexity of real sea-ice algae communities. This dissertation investigates the effects of three sea-ice algae transportation methods on the concentration development of sea-ice algae, as well as the potential for experimentation with the algae transported with these methods. Two methods were adapted from literature: transportation in solid (1) and liquid (2) environments. In addition to these methods, a third method was explored: Transportation of living sea-ice algae in a hybrid solid-liquid system. The aim of transporting in the hybrid system was to minimise the changes from the natural to the artificial environment. Solid sea-ice storage was evaluated by means of an artificial sea-ice study: Artificial sea ice was grown, extracted and stored at -20 °C for 7 different durations, between 0 minutes and 35 weeks. Samples were segmented into 20 mm thick slices, melted, analysed for salinity and brine profile development was assessed. It was found that storage significantly impacted brine profiles, causing an average bulk desalination of 19% between samples stored for 1 day and 35 weeks, as well as a change in the shape of the salinity profile from a W to a C shape. Solid sea-ice transportation was thus eliminated as a transportation method for this work due to the high change algae communities would likely undergo during due to desalination and unfavourable environmental conditions associated with low temperatures. A solid-liquid hybrid system for the transportation of sea-ice algae was designed and constructed, consisting of a 30 litre Perspex tank, insulation, and a heating system. Two sea-ice cores were obtained from the Southern Ocean in winter of 2019 and transported in the hybrid system to land facilities. Issues with the system were identified, dedicated lights added, and an additional hybrid tank constructed. Six sea-ice cores were obtained from the Southern Ocean in spring of 2019 and parts of them transported in the hybrid tanks to land facilities, where they were melted and cultured in a liquid environment for 56 days. Sections of the cores were melted, and the algae preserved before transportation. Algae concentrations were determined via microscopy of preserved samples taken before transport, after transport and after liquid culturing. Taxonomic distributions of algae varied greatly between initial samples and concentrations ranged from 46 000 to 1 200 000 cells per ml. The hybrid transportation method caused the lowest degree of change in the community compositions and increased the overall concentrations of algae, whilst liquid incubation mostly decreased algae concentrations.